Optical and structural properties of lithium sodium borate glasses doped Dy3+ ions - Said Dawaud, Raghda Saeif Eddin; Hashim, Suhairul; Alajerami, Yasser Saleh Mustafa; Mhareb, M. H. A.; Tamchek, Nizam (Elsevier, 2014)
Absorption and emission spectra of lithium sodium borate glass doped with different concentrations of Dy3+ have been reported. The concentration of Dy3+ was varied from 0.3 to 1.3 mol%. The amorphous nature of the prepared samples was confirmed by the X-ray Diffraction (XRD). Fourier transforms infrared (FTIR) spectra, and other significant physical properties (energy band gap, density, ion concentration, molar volume, Polaron radius and inter-nuclear distance) have been analyzed in the light of the different oxidation states of the co-dopant ions. The absorption spectrum showed nine peaks with hypersensitive transition corresponding to 6F11/2 + 6H9/2 at 1256 nm. As a result of 380 nm excitation wavelength, the luminescence spectra showed two characteristic bands at 479 nm and 587 nm. These absorption bands were attributed to 6P15/2 → 6H15/2 and 6P15/2 → 6H13/2 transitions of trivalent Dy3+ ions. The current study indicates that Dy doped lithium sodium borate glasses are attractive for solid-state laser applications.